Repeat biopsy versus initial biopsy in terms of complication risk factors and clinical outcomes for patients with non-small cell lung cancer: a comparative study of 113 CT-guided needle biopsy of lung lesions - Wang, Yangyang; Zhang, Yongyuan; Ren, Nana; Li, Fangting; Lu, Lin; Zhao, Xin; Zhou, Zhigang; Gao, Mengyu; Wang, Meng (Frontiers in Oncology, 2024)
Objectives The safety and feasibility of repeat biopsy after systemic treatment for non-small cell lung cancer have received extensive attention in recent years. The purpose of this research was to compare complication rates between initial biopsy and rebiopsy in non-small cell lung cancer patients with progressive disease and to assess complication risk factors and clinical results after rebiopsy. Methods The study included 113 patients initially diagnosed with non-small cell lung cancer who underwent lung biopsy at initial biopsy and rebiopsy after progression while on epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) and/or chemotherapy from January 2018 to December 2021. We compared the incidence of complications between the initial biopsy and rebiopsy and analyzed the predictors factors that influenced complications in patients who underwent rebiopsy. Results The successful rate of rebiopsy was 88.5% (100/113). With the exception of two cases where lung adenocarcinoma changed into small cell lung cancer with gefitinib treatment, 98 individuals retained their initial pathological type. The secondary EGFR T790M mutation accounts for 55.6% of acquired resistance. The total number of patients with complications in initial biopsy was 25 (22.1%) and 37 (32.7%) in the rebiopsy. The incidence of pulmonary hemorrhage increased from 7.1% at the initial biopsy to 10.6% at rebiopsy, while the incidence of pneumothorax increased from 14.2% to 20.4%. Compared with the initial biopsy, the incidence of overall complications, parenchymal hemorrhage, and pneumothorax increased by 10.6%, 3.5%, and 6.2%, respectively. In all four evaluations (pneumorrhagia, pneumothorax, pleural reaction, and overall complication), there were no significant differences between the rebiopsy and initial biopsy (all p > 0.05). The multivariate logistic regression analysis suggested that male sex (odds ratio [OR] = 5.064, p = 0.001), tumor size ≤ 2 cm (OR = 3.367, p = 0.013), EGFR-TKIs with chemotherapy (OR = 3.633, p =0.023), and transfissural approach (OR = 7.583, p = 0.026) were independent risk factors for overall complication after rebiopsy. Conclusion Compared with the initial biopsy, the complication rates displayed a slight, but not significant, elevation in rebiopsy. Male sex, tumor size ≤ 2 cm, transfissural approach, and EGFR-TKIs combined with chemotherapy were independent risk factors for rebiopsy complications.